Éagóir : Maolra Seoighe agus dúnmharuithe Mhám Trasna. - Ó Cuirreáin, Seán (Cois Life, 2016)
The retelling of the story of barbaric murders in the quiet rural area of Joyce country in Connemara over 100 years ago and the unjust conviction and hanging of innocent men that followed.